About psychosocial vulnerabilities and strengths psychosocial - Santini, Oscar Alfredo (2016)
This article aim to describe the psychological work associated with events that could produce a disruptive impact and collapse the responsiveness of organisms. Emphasis is given to the rigorous care required in conducting assessments from a pre-diagnostic linear reading in relation to emotional and material impact. Hence, the importance of the containment capacity and primary bras, which will define the significant primary links, is highlighted. In the same line, solidarity and community participation are highlighted as nerve-wracking, generating significant links that will face destructive paths. Thus, the advantages of prevention for the whole process of Disaster Risk Integral Management and the participatory elaboration of the Local Risk Map are highlighted as an important integral and integrated Preventive Psychosocial Strategy. Finally, the work of humor is raised as a resource of excellence to regulate stress, suffering, self-esteem crises, frustrated experiences and even the sinister.